2014
DOI: 10.1007/s11255-014-0685-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depression and anxiety in patients with end-stage renal disease receiving maintenance hemodialysis

Abstract: History of alcohol consumption may predict less depressive symptoms and more anxiety among Chinese patients living in a northeastern Chinese city with ESRD. EPO administration may reduce anxiety in patients with ESRD. Female patients were more prone to anxiety, whereas males were more likely to show symptoms of depression. These factors should be evaluated by nephrologists treating patients with ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 25 publications
5
36
1
1
Order By: Relevance
“…A total of 81 patients were included in the study. Using the self-rating anxiety scale and depression self-assessment scale questionnaires, the results showed that female patients were more likely to develop anxiety, whereas males were more likely to show depressive symptoms [19]. Another recent study conducted in Korea involving 973 subjects aged ≥65 years found that the prevalence of depression in elderly women is higher than in men regardless of CKD stage [20].…”
Section: Discussionmentioning
confidence: 97%
“…A total of 81 patients were included in the study. Using the self-rating anxiety scale and depression self-assessment scale questionnaires, the results showed that female patients were more likely to develop anxiety, whereas males were more likely to show depressive symptoms [19]. Another recent study conducted in Korea involving 973 subjects aged ≥65 years found that the prevalence of depression in elderly women is higher than in men regardless of CKD stage [20].…”
Section: Discussionmentioning
confidence: 97%
“…61 In terms of ethnicity, white patients, as compared to African-American patients, were at higher risk of depression. 11,62 In a study by Yoong et al in Singapore, Chinese patients were found to be more likely to develop depression than those of Malay and other ethnicities.…”
mentioning
confidence: 99%
“…For instance, patients with depressive symptoms were also found to have other comorbid illnesses such as diabetes mellitus, hypertension, cardiovascular heart disease, hypoalbuminemia, and substance abuse. 8,61,62 An increased risk of depression and anxiety has also been associated with adverse outcomes in kidney transplantation. Kidney graft rejection has been reported to trigger feelings of depression, anxiety, aggression, and loss.…”
mentioning
confidence: 99%
“…For example, the depressive symptoms of decreased appetite or fatigue, sleep disturbance, and pain are often difficult to distinguish from the symptoms of MHD patients. Unfortunately, many self‐report depression scales, such as the BDI , the SDS , and the CES‐D , include some of these symptoms. To our knowledge, these results are the first to show a high level of overlap between depressed and nondepressed MHD patients in terms of the somatic symptoms of appetite or fatigue change, sleep disturbance, and lower sex drive ( P > 0.05) using comparative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, such interviews must be administered by trained health professionals, and they are time‐consuming and difficult to apply in routine clinical practice . Moreover, a large body of literature describes the use of various self‐administered depression screening scales, including the Beck Depression Inventory (BDI) , the Self‐Rating Depression Scale (SDS) , and the Center for Epidemiological Studies Depression Scale (CES‐D) , to identify depression in chronic dialysis patients. However, MHD patients may experience increased somatic symptoms, such as fatigue, poor appetite, and sleep disturbance, that may not be associated with a depressive disorder .…”
mentioning
confidence: 99%